Improved Microprocessor Control Device for Diesel Locomotive - 刘松柏; 张东方; 谢小婷; 李玮斌; 赵军伟 (机车电传动)
This paper introduced the hardware structure, system function and the advantages of the improved microprocessor control device for diesel locomotive, which resolved the actual market needs of small and modular for microprocessor control device for diesel locomotive. On-site examination proves that the control device is stable and reliable, cost-effective, easy to maintain and repair.